Analisis Manajemen Persediaan Bahan Baku Pada UMKM Risol Kekasih Pekalongan - Gunawan Aji; Hilda Shafira; Shyva Khofifatuz Zahro; Arny Juliyanti (BADAN PENERBIT STIEPARI PRESS, 2023)
Inventory management is an important role for management accountants in presenting data to internal company parties. This data has vital uses in the management decision-making process related to the company's operational performance. The aim of this research is to determine the management of raw material supplies at the UMKM Risol Kekasih Pekalongan. The type of approach used is descriptive qualitative, where the researcher analyzes the inventory management in the UMKM Risol Kekasih Pekalongan using the EOQ, Safety Stock and ROP analysis methods. The data used is primary data obtained by interviews and observations as well as secondary data. The results of this research show that the EOQ yield is 592 kg of wheat which can be ordered, and is carried out 7 times per year with Re-orders (ROP) carried out when the remaining inventory is 12 kg. In inventory management, of course there are various aspects that influence whether inventory management is effective or not. This calculation is an alternative to find out how much inventory must be in the warehouse and how much must be ordered by taking into account ordering costs and storage costs.